2023
DOI: 10.1021/acsestwater.2c00652
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances in Field-Collected Light Non-Aqueous Phase Liquids

Abstract: Per-and polyfluoroalkyl substances (PFAS) and non-aqueous phase liquids (NAPLs) co-occur at sites where aqueous film forming foams (AFFFs) were used as part of firefighter training exercises or in response to emergencies (e.g., crashes). Till date, there are no data on PFAS in field-collected, light NAPLs (LNAPLs) recovered from groundwater wells on US military bases. Analytical methods were developed for target and suspect nonvolatile (anionic) and volatile (neutral) PFAS in field-collected LNAPLs. The valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Similarly, the surfactant behavior of PFASs could impact their distribution among phases throughout the vadose zone also. How does the co-occurrence of other contaminants (e.g., other AFFF components, solvents) modify the accumulation of FtOHs, FOSAs, and FOSEs at the groundwater table, which could impact the availability of vapor-phase PFASs in soil gas in source zones and down-gradient locations? Christie et al reported data demonstrating that certain PFASs were present in less-dense-than-water non-aqueous phase liquids (LNAPLs) that were recovered from groundwater wells on US military bases where AFFFs were used. Whereas “only one had quantifiable neutral PFAS (6:2 fluorotelomer alcohol)” in their study, it is conceivable that such LNAPLs influence the volatilization of a variety of PFASs into overlying soil at other sites where AFFFs were used.…”
Section: Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the surfactant behavior of PFASs could impact their distribution among phases throughout the vadose zone also. How does the co-occurrence of other contaminants (e.g., other AFFF components, solvents) modify the accumulation of FtOHs, FOSAs, and FOSEs at the groundwater table, which could impact the availability of vapor-phase PFASs in soil gas in source zones and down-gradient locations? Christie et al reported data demonstrating that certain PFASs were present in less-dense-than-water non-aqueous phase liquids (LNAPLs) that were recovered from groundwater wells on US military bases where AFFFs were used. Whereas “only one had quantifiable neutral PFAS (6:2 fluorotelomer alcohol)” in their study, it is conceivable that such LNAPLs influence the volatilization of a variety of PFASs into overlying soil at other sites where AFFFs were used.…”
Section: Research Needsmentioning
confidence: 99%
“…Christie et al 36 reported data demonstrating that certain PFASs were present in less-dense-than-water non-aqueous phase liquids (LNAPLs) that were recovered from groundwater wells on US military bases where AFFFs were used. Whereas "only one had quantifiable neutral PFAS (6:2 fluorotelomer alcohol)" in their study, 36 it is conceivable that such LNAPLs influence the volatilization of a variety of PFASs into overlying soil at other sites where AFFFs were used. Titaley et al 9 noted that the impacts of butyl carbitol, a relatively abundant component of certain AFFFs, on biotransformation of FtOHs "are not known and represent a knowledge gap".…”
Section: ■ Introductionmentioning
confidence: 99%